2007
DOI: 10.1007/s11832-007-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

Flexible intramedullary nailing for unicameral cysts in children's long bones

Abstract: Purpose The purpose of this study was to evaluate the outcome of flexible intramedullary nailing for unicameral bone cysts in terms of function and osseous consolidation. Methods Twenty-two unicameral bone cysts in children's long bones were treated by flexible intramedullary nailing. In 13 cases the bone cyst was diagnosed in a traumatic event leading to a pathologic fracture. Fifteen patients were referred to our clinic after failed conservative treatment. In 16 patients the cyst was located in the humerus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…Excellent healing rates were reported by Roposch, [6] Givon, [7] Masquijo, [8], and Glanzmann [9]. Since then, these authors have achieved higher complete healing rates (89%), and this radiologic result of the treatment was shown 8.7 months after surgery.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Excellent healing rates were reported by Roposch, [6] Givon, [7] Masquijo, [8], and Glanzmann [9]. Since then, these authors have achieved higher complete healing rates (89%), and this radiologic result of the treatment was shown 8.7 months after surgery.…”
Section: Discussionmentioning
confidence: 70%
“…The main goal of treatment is thus the prevention of pathologic fractures, support of the healing process, and prevention of recurrence. Recent studies have reported excellent results with flexible nailing [5][6][7][8][9]; therefore, we designed a prospective study to examine the efficacy of flexible intramedullary nailing for the prevention of pathologic fracture, stabilization of SBC, and promotion of lesion healing. Although earlier wide resections with or without bone grafts were performed, current concepts are based on less invasive and aggressive treatment strategies [4].…”
Section: Introductionmentioning
confidence: 99%
“…While there are a handful of adult case series reporting excellent healing with Enders nails [13,14], there are no dedicated reports in the pediatric literature describing the results of this technique and its complications [10][11][12]. Several small case series have shown the efficacy of this implant in treating pathologic humeral shaft fractures in children and, in particular,in promoting healing in unicameral bone cysts [15][16][17]. The aim of this report is to describe the technique and results of operative stabilization of pediatric humeral shaft fractures with titanium elastic nails.…”
Section: Introductionmentioning
confidence: 99%
“…By providing a continuous drainage between the medullary canal and the cyst cavity, elastic nails can reduce intracystic pressure and stimulate healing [26][27][28]. Elastic nails can also stabilize the pathological fractures [12,[29][30][31][32]. However, healing with a residual cyst is a frequent finding following isolated use of intramedullary nailing [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%